Pulmonary Artery Catheter Versus Central Venous Catheter in Patients Undergoing Beating Heart Coronary Artery Bypass Surgery: A Comparative Approach - Pushkar Desai; Shirish Mahure; Manjula Sarkar; Sanjeeta Umbarkar (New Frontiers in Medicine and Medical Research Vol. 7, 2021)
Background: Central venous and pulmonary artery catheter are integral part of hemodynamic monitoring during off pump coronary artery bypass grafting surgery. Methods: In this prospective randomized trial, sixty patients were divided equally into two groups, to receive either central venous or pulmonary artery catheter after induction of anesthesia with high dose of opioid and Inj pancuronium. Patients between 35-65 years with ejection fraction 40-60% undergoing elective off pump coronary artery bypass surgery were included while those with left ventricular dysfunction were excluded. All patients were operated by same team of surgeons. Systolic blood pressure (SBP) and/or mean arterial pressure (MAP) was kept above 90 and 60 mm Hg respectively throughout perioperative period by fluid volume expansion and inotropic support. Nitroglycerine was used for blood pressure control and coronary vasodilation. Both groups were compared with respect to intervention requiring inotropes and its duration, ICU stay and any complications occurred. Results: Significant number of patients in CVP group were started on inotropes than PAC group (66.6% vs 40%, P=0.038). Among these, 75% in Gr. A needed it for less than 24 hours compared to 65% in Gr. B. Both groups needed similar trials of fluid challenge [40% vs 53.33%; P=0.30] and showed similar duration of intensive care unit stay (more than 48 hrs) [66.67% vs 53.3%; p=0.29, chi square test]. More number of patients developed complications in CVP group [6.6 vs 16.6%; P=0.22]. One patient in each group had mortality. Conclusion: PA catheter guided management does not provide additional benefit over CVP guided management alone during OPCAB surgery in patients with preserved LV function.